Formation of active surface of copper catalysts in methanol oxidation; The 7th International Forum on Strategic Technology (IFOST-2012), September 18-21, 2012, Tomsk - Pestryakov A. N. Aleksey Nikolaevich; Lunin V.; Temkin O.; Derusova D. A. Dariya Aleksandrovna; Bogdanchikova N.; Petranovskii V. (2012, 2012)
Title screen